Peran Pelabuhan Kuno di Flores Timur dalam Jalur Perdagangan Nusantara pada Abad XVI-XVII - I Wayan Sumerata; Hedwi Prihatmoko; Ida Ayu Gede Megasuari Indria; J. Susetyo Edy Yuwono; I Made Pageh (PURBAWIDYA: Jurnal Penelitian dan Pengembangan Arkeologi, 2022)
Geographically, East Flores Regency covers the eastern part of Flores Island, Solor Island, and Adonara Island. This study focuses on the three old ports, namely Larantuka Port (located in the eastern part of Flores Island), Lohayong Port (located in Solor Island), and Adonara Port (located in Adonara Island). These three ports have been used as parts of maritime trade routes during colonial period. The purpose of this study is to reconstruct the function of these ports during 16th to 17th century, which were based on archaeological remains, geographical, and enviromental data. These ports are closely related to the availability of the superior commodity found in eastern Flores, namely sandalwood. The shipping lanes formed from several ports were reconstructed using maps. Most of the ports that have been researched in this region are traditional ports which has been used since Portuguese occupation of East Flores. Each port has different roles according to its location and association with supporting findings. Most of the old ports are collector ports on a local scale, except for Larantuka Port which was on an international scale. These ports are not only evidence of maritime activities, but also become nodes for unraveling the political, economic, and social aspects of civilization.